GAMBARAN PERILAKU BELAJAR SISWA KELAS VIII.2 DALAM PEMBELAJARAN IPS DI SPMN 1 AMPEK NAGARI KABUPATEN AGAM - FITRI, SALMA - (Pendidikan Sejarah, 2014)
The first survey in 2013 toÂ  10 students was found 8 students (80%) have unfavorable behavior in social learning as they often ask for pennission to leave , chatting while studying and did not record what was explained by social studies teacher. While 2 others have good manners in social learning. This study used a qualitatively research by case study. The infonnants in this study is, Principals, social studies teacher , and Vlll .2 Grade Students in Social Learning in SMPN I Ampek Nagari Kabupaten Agam. The data collected in this study is primary data obtained through interviews. The data analysis technique used consists of a phase reduction, data presentation I analysis of data, and conclusion. The results of the study found 6 students have good grades in a listening the teacher, while 14 students have considerableÂ  value in a listening to the teacher, 3 students have good grades in noting the lessons provided by the teacher which meant only 3 students who recorded the lessons given by the teacher, two students were really paying attention to the lessons given by the teacher, most students there are not really paying attention to what given by the teacher. There are I 0 students that make the task group and I 0 students another did not make the task group. Teachers should be able to anticipate the learning process in the preparation of social studies using the media so that the learning process does not become monotonous and boring social studies for students.